The Effect of Peer and Self-Assessment on the Presentation Skills of Grade 5 Students in an International School - Lunar, Abraham; Mascuñana, Chona; Bual, Joel (Technium Social Sciences Journal, 2024)
Presentation skills encompass the abilities and qualities necessary for crafting and delivering compelling content that effectively conveys information and ideas. Mastering these skills is crucial for initiating change, promoting collaboration, and effective communication across diverse contexts, with presentations playing a vital role in fostering positive learning experiences. Anchored on self-determination theory and social learning theory, this study determined the effect of peer and self-assessment on the presentation skills of Grade 5 students. Utilizing a quasi-experimental, non-equivalent control group pretest-posttest design, the presentation skills of 45 groups of students, assigned as control and experimental groups using simple random sampling, were assessed with a validated and reliability-tested rubric. For data analysis, Kolmogorov-Smirnov was used for the normality test, independent samples t-test, Wilcoxon signed rank test, and Quade’s analysis for inferential statistics. Peer and self-assessment interventions significantly improve presentation skills among students during the PYP exhibition. While initial differences existed between the experimental and control groups, both groups showed substantial improvements post-intervention, with the experimental group exhibiting notably higher performance compared to the control group. With these results, the theories are validated, highlighting the significant integration of peer and self-assessment into teaching approaches, which plays a crucial role in fostering students’ presentation skills during the PYP exhibition.